Enterprise architecture breakthrough for telecommunications transformation: A reconciliation model to solve bankruptcy - Dachyar, M.; Zagloel, Teuku Yuri M.; Saragih, L. Ranjaliba (Heliyon, 2020)
Observations of communication service providers (CSPs) over the past five years have revealed that text services have reduced radically by around 75%, followed by voice services and the average revenue per user (ARPU). This condition signifies that telecommunications companies are being affected by digital disruption. A fundamental analysis of current business processes is thus necessary for future telecommunications success. In the area of corporate strategic management, studies on conversion of the Internet of Things (IoT)-based industry as a new customer are gaining popularity. This research analyzes the breakthrough operational activities through a customer-centric approach as well as end-to-end CSP business activities towards a new customer reconciliation model. The customer-centric activities address problem to solution and complaint to solution. In the future, CSPs are expected to have large numbers of newly registered customers from IoT-based industries. The strategic mechanism for transforming leaps from old business processes into new ones is a novel research subject using the business process management (BPM) method. Business process analysis has been facilitated by the Internationa Telecommunication Union (ITU) telecommunications standards body developed by TMForum as the global telecommunications industry association. This transformation involves development of organizational structure, business activities, technical specifications, information and communication flow, and operational schemes, modeled under the enterprise architecture strategic notation, whose result is a breakthrough enterprise architecture design for future telecommunications companies. The design contributes to strategic management knowledge on how collaboration between the telecommunications industry and other IoT-based industries is determined for real operations. This research presents a transformation scheme that can solve the potential problem of bankruptcy in the telecommunications industry through a case study of a smart city in the IoT-based industry. Electrical engineering; Industry; Industrial engineering; Internet of things; Process modeling; Operations management; Industry management; Strategic management; Telecommunication companies; Business process management (BPM); Enterprise architecture; Internet-of-things (IoT).